Detection of helicoidal motion in the optical jet of PKS 0521−365. (7th June 2017) - Jiménez-Andrade, E. F.; Chavushyan, V.; León-Tavares, J.; Patiño-Álvarez, V. M.; Olguín-Iglesias, A.; Kotilainen, J.; Falomo, R.; Hyvönen, T.
Abstract: The jet activity of active galactic nuclei (AGNs), and its interaction with the interstellar medium, may play a pivotal role in the processes that regulate the growth and star formation of its host galaxy. Observational evidence that pinpoints the conditions of such interaction is paramount to unveil the physical processes involved. We report on the discovery of extended emission-line regions exhibiting an S-shaped morphology along the optical jet of the radio-loud AGN PKS 0521−365 ( z = 0.055), by using long-slit spectroscopic observations obtained with FOcal Reducer/low dispersion Spectrograph 2 on the Very Large Telescope. The velocity pattern derived from the [O ii ] λ3727 Å, H β λ4861 Å and [O iii ] λλ4959, 5007 Å emission lines is well fitted by a sinusoidal function of the form: v ( r ) = α r 1/2 sin(β r 1/2 + γ), suggesting helicoidal motions along the jet up to distances of 20 kpc. We estimate a lower limit for the mass of the outflowing ionized gas along the jet of ∼10 4  M⊙ . Helical magnetic fields and jet precession have been proposed to explain helicoidal paths along the jet at pc scales; nevertheless, it is not clear yet whether these hypotheses may hold at kpc scales.